The Consumer Society and the (False) Myth of Mass Democratisation - Marchetti, Maria Cristina (Italian Sociological Review, 2017)
About fifty years from its first publication in 1970, La société de consommation. Ses mythes ses structures (Paris Denoël) confirms itself as a lucid analysis of the meanings at the basis of the consumption dynamics within contemporary society. In what he calls the ‘mystique of equality’, the concept of needs is linked to that of well-being, triggering the illusion that the increase in total amount of goods an individual can possess automatically translates into a levelling of society and in total well-being for all. According to Baudrillard, this approach does not take due account of the social logic of consumption, at which level the differentiation process for the retention of social distances is reiterated. Thus, according to Baudrillard, a mechanism that powers social differences survives through a consumerist ideology disguised as egalitarianism. Hence, Baudrillard distances himself from Marx and from the concept of value in use, understanding that at the base of mature capitalism does not lie production (and thus the dialectic of capital/labour force), but consumption. Years later, the system of consumption presents itself unchanged, to the extent that in some respects the postmodern aesthetics has actually exasperated its characteristics, blending the needs of production with an individual differentiation process that seems incapable of finding other ways of expression.